2019
DOI: 10.1038/s41598-019-39861-4
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix-bound nanovesicles prevent ischemia-induced retinal ganglion cell axon degeneration and death and preserve visual function

Abstract: Injury to retinal ganglion cells (RGC), central nervous system neurons that relay visual information to the brain, often leads to RGC axon degeneration and permanently lost visual function. Herein this study shows matrix-bound nanovesicles (MBV), a distinct class of extracellular nanovesicle localized specifically to the extracellular matrix (ECM) of healthy tissues, can neuroprotect RGCs and preserve visual function after severe, intraocular pressure (IOP) induced ischemia in rat. Intravitreal MBV injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 59 publications
1
34
0
Order By: Relevance
“…MBVs are integral and distinct components of ECM, and their content is unique to cellular origin (78). Recently, it has been demonstrated that MBVs can suppress pro-inflammatory signaling in microglia and astrocytes (79). So far, the literature exists only on MBVs found in non-timorous ECM, but we propose that tumor-specific MBVs may also be found.…”
Section: Extracellular Vesicles As Cancer Biomarkers and Regulators Omentioning
confidence: 88%
“…MBVs are integral and distinct components of ECM, and their content is unique to cellular origin (78). Recently, it has been demonstrated that MBVs can suppress pro-inflammatory signaling in microglia and astrocytes (79). So far, the literature exists only on MBVs found in non-timorous ECM, but we propose that tumor-specific MBVs may also be found.…”
Section: Extracellular Vesicles As Cancer Biomarkers and Regulators Omentioning
confidence: 88%
“…MBVs and their miRNA cargoes can recapitulate many of their parent ECM’s effects, including the promotion of a regulatory macrophage phenotype, thus facilitating tissue repair [ 22 ]. In addition, MBVs have been shown to positively regulate primary neuron survival and growth [ 25 ] as well as to reduce proinflammatory, neurotoxic glial signaling enhancing healing responses in the retina and the optic nerve [ 26 ]. Although PDNVs were initially conceived as more similar in structure and function to mammalian exosomes than MBVs [ 27 ], they are quite heterogeneous in size (see below) and may have distinct features from mammalian exosomes and MBVs.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese-enhanced MRI also provides a solution to non-invasively image transport deficits in the visual system for examining neuronal abnormalities caused by optic neuropathies such as irradiation-induced injuries (Ryu et al, 2002), optic nerve crush (Thuen et al, 2005; Fischer et al, 2014), glaucoma (Chan et al, 2007, 2008c; Fiedorowicz et al, 2018; Yang et al, 2018), optic neuritis (Lin et al, 2014b), retinal ischemia/reperfusion (van der Merwe et al, 2019), and neonatal hypoxia-ischemia (Chan et al, 2014b). Studies by Thuen et al (2005, 2009) are among the earliest to demonstrate the feasibility of MEMRI for longitudinal monitoring of Mn 2+ transport along injured axons of the central visual pathway via intraocular Mn 2+ administration.…”
Section: Neuronal Tract Tracingmentioning
confidence: 99%
“…Subsequent studies demonstrated the use of in vivo MEMRI tract tracing for retinotopic mapping at submillimeter resolution (Chan et al, 2011) (Figure 3B), and for monitoring primary versus secondary degeneration after partial transection of the optic nerve (Chan et al, 2017). With these premises, MEMRI can serve as an in vivo imaging model system to evaluate neuroprotective approaches to the injured visual system (Mansergh et al, 2014; Van der Merwe et al, 2016, van der Merwe et al, 2019), as well as to trace neuroplasticity (Immonen et al, 2008; Chan et al, 2012a; Tang et al, 2017b) and regenerated axons along the visual pathway (Liang et al, 2011; Sandvig et al, 2011, 2012; Sandvig and Sandvig, 2014; Komatsu et al, 2017). MEMRI can be combined with diffusion tensor imaging to give complementary information about injury and regeneration in the adult optic nerve (Thuen et al, 2009).…”
Section: Neuronal Tract Tracingmentioning
confidence: 99%
See 1 more Smart Citation